Differences in the vegetation dynamic patterns of three tropical secondary forests in South Sulawesi, Indonesia - PUTU SUPADMA PUTRA; TOSHIHIRO YAMADA; AMRAN ACHMAD; NASRI NASRI; ANDI SIADY HAMZAH; PUTU OKA NGAKAN (Society for Indonesian Biodiversity, 2023)
Abstract. Putra PS, Yamada T, Achmad A, Nasri N, Hamzah AS, Ngakan PO. 2023. Differences in the vegetation dynamic patterns of three tropical secondary forests in South Sulawesi, Indonesia. Biodiversitas 24: 5065-5073. Degraded forests experience dynamics that drive them towards stable ecological conditions as a result of the succession process. Understanding the dynamics of forests through succession is a requirement for secondary forest management activities. The purpose of this research was to uncover the dynamics of population, species composition, and dominance in three secondary tropical forest communities: (i) Karst forest, (ii) Lowland forest, and (iii) Pinus merkusii plantation forest. Permanent plots with areas tailored to the richness of each forest community were constructed, and vegetation studies were conducted annually from 2019 to 2022. The results revealed that the ten most dominant species in each plot shared only one species. The rest were exclusive to a single community. During the four years of research, 25 out of a total of 90 species (Karst), 27 out of a total of 68 species (Lowland), and 12 out of a total of 43 species (Pine) experienced dynamics in the form of an increase or decrease in population. Tree density decreased in the Karst plot and fluctuated slightly in the Lowland and Pine forest plots. Meanwhile, the basal area cover continued to increase during the 4 years of observation. Comparing age and pre-succession land use history, soil type and restoration history appear dominant in determining the forest dynamics.